Impact of E-Government Development on the Level of Corruption: Measuring the Effects of Related Indices in Time and Dimensions - Renáta Máchová; Jolana Volejníková; Martin Lněnička (Review of Economic Perspectives, 2018)
E-government is recognized as a tool for improving transparency and openness in the public sector and for combatting corruption. Understanding the relationship between e-government development and the level of corruption would allow for a more effective leveraging of related projects in anti-corruption efforts. This paper examines the impact of e-government development on the level of corruption in the context of economic perspective. In contrast to previous studies, this empirical relationship is measured across sub-indices (dimensions) of related indices between 2002 and 2016. The results show that higher levels of e-government development are related to lower levels of corruption. The three most important dimensions found are the environment sub-index, which assesses the extent to which a country's market conditions and regulatory framework support entrepreneurship, innovation, and ICT development; the usage sub-index, which assesses the level of ICT adoption by a society's main stakeholders; and the telecommunication infrastructure sub-index measuring a country's ICT infrastructure capacity. Following these findings, certain ways of influencing of the level of corruption by a stimulation of concrete e-government development dimensions can be drawn. This is important especially in the time of a financial crisis and its consequences, which are also discussed in this paper.
Keywords: 330; correlation analysis; corruption; dimensions; e-government development; indices; regression models